Implementasi Pengelolaan Data Keuangan Menggunakan MYOB Accounting V18 pada King’s Computer - Wati Erawati (Labkat Press KA FTIK UNIKOM, 2021)
The technology deveploment in the current era of globalization has provided many benefits in progress various aspects of human life, especially in the field of technology and communication, as evidenced by the inventions of software or devices that support work in the accounting field. For this reason, this research is about processing accounting data at King’s Computer store,which until now has not been effective and efficient in processing data at the store. King’s computer store is a store that is engaged in sales, maintenance and computer service services whose financial transaction processes are still carried out manually, namely by recording on paper or in books. Often there is loss of proof of transactions and errors in the recording process, this results in the slow process of making the required financial statements. Manual accounting data processing has more risks than a computerized system. Then this computer system application can be alternative problem solving in processing accounting data at this store. By using the MYOB (Mind Your Own Business) Accounting Plus v18 ED application the user can find out the company’s accounting information more accurately and quickly and help the company’s operational activities in data processing and providing financial reports so that it runs more effectively and efficiently and can avoid data security problems store financial data. The use of MYOB requires accuracy and discipline from the user, especially when inputting data so that the output produced is as expected. Users are also strongly advised to do a Daily Backup to avoid data loss. In addition, the author also suggests sufficient training for employees so that they will optimize work using the MYOB Accounting Plus V18 software.